2023
DOI: 10.1108/ijge-05-2021-0079
|View full text |Cite
|
Sign up to set email alerts
|

Women entrepreneurs in India: a systematic literature review

Abstract: PurposeThis paper aims to organize the existing empirical research on women entrepreneurs (WEs) in India, highlight the research areas that have not received attention and present opportunities for future research.Design/methodology/approachA systematic literature review (SLR) was performed on 74 scholarly articles focusing on WEs in India and published between 1993 and 2020. This review is structured around the 4W framework used in previous SLRs. The review is directed by the following foci: what do we know a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 146 publications
0
12
0
Order By: Relevance
“…In the previous studies which were conducted in India, challenges were identified and the reasons behind them were also explored; challenges are as follows: lack of regulation or law, lack of formal education, financial resources (Koutoupis et al, 2023), skilled labor, informal financing, role models, networking, training and education, lack of work-life balance, ease of entry, discrimination and assessing technology (Agrawal et al, 2023;Baral et al, 2023;Rastogi et al, 2022;Noor et al, 2022;Pradhan, 2019;Shastri et al, 2022;Tripathi and Singh, 2018;Khandelwal and Sehgal, 2018). The reasons behind these problems are gender biases, societal norms, competition from larger firms, cultural and social norms and lack of awareness, skills and infrastructure (Chaudhari et al, 2020).…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies which were conducted in India, challenges were identified and the reasons behind them were also explored; challenges are as follows: lack of regulation or law, lack of formal education, financial resources (Koutoupis et al, 2023), skilled labor, informal financing, role models, networking, training and education, lack of work-life balance, ease of entry, discrimination and assessing technology (Agrawal et al, 2023;Baral et al, 2023;Rastogi et al, 2022;Noor et al, 2022;Pradhan, 2019;Shastri et al, 2022;Tripathi and Singh, 2018;Khandelwal and Sehgal, 2018). The reasons behind these problems are gender biases, societal norms, competition from larger firms, cultural and social norms and lack of awareness, skills and infrastructure (Chaudhari et al, 2020).…”
Section: Challengesmentioning
confidence: 99%
“…, 2023), skilled labor, informal financing, role models, networking, training and education, lack of work-life balance, ease of entry, discrimination and assessing technology (Agrawal et al. , 2023; Baral et al. , 2023; Rastogi et al.…”
Section: Women Entrepreneurs In Indiamentioning
confidence: 99%
“…There is a growing body of research on women entrepreneurship [11][12][13][14][15][16] and participation of women in agriculture and Agripreneurship in India. [17][18][19][20][21][22] However, there is still limited understanding of the status of WA and the factors influencing women's involvement in the AC&ABC scheme and the potential benefits of their increased participation in this initiative.…”
Section: Introductionmentioning
confidence: 99%
“…Women entrepreneurs continue to confront tremendous obstacles in obtaining financial resources and ending the cycle of poverty, particularly in emerging nations, even in the face of notable advancements in women's empowerment efforts (Winn, 2005). Their ambitions to become financially independent and entrepreneurs are hampered by a lack of loan availability, a lack of financial awareness, and deeply rooted gender biases (Baral et al, 2023). The general socioeconomic development of communities is hampered by this lack of financial inclusion, which also maintains gender inequities and stunts the growth of womenled companies.…”
Section: Introductionmentioning
confidence: 99%